The relation between the serological similarity of proteins and the adsorption of particles of Pectobacterium carotovorum J2 bacteriocins and bacteriophage ZF40 - Maksymenko, L.A.; Romaniuk, L.V. (Reports of the National Academy of Sciences of Ukraine, 2016)
Immunoblot analysis with rabbit antiserum has revealed serologically related protein components in the structure of phage tail-like macromolecular carotovoricins (MCTV/J2) and bacteriophage ZF40 Pectobacterium carotovorum subsp. carotovorum. These components may act as recognition factors for the common binding sites on the bacterial surface. A competition for the adsorbtion sites between the phage ZF40 and MCTV/J2 is demonstrated under the conditions of mixed infection.